Wageningen Statement on Gender and Agriculture in the Information Society (13-09-02) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Gender and rural development have a Cinderella status in the international debate on sustainable development.